Delineation of Natural and Anthropogenic Process Controlling Hydrogeochemistry of Layered Aquifer Sequence - Thilagavathi, R.; Chidambaram, S.; Thivya, C.; Prasanna, Mohan Viswanathan; Singaraja, C.; Tirumalesh, K.; Pethaperumal, S. (Springer, 2014)
Groundwater is the source for many activities in urban regions and the quality plays a significant role in determination of its usage. In coastal regions the situation becomes more complex due to the interplay of complex chemical processes like natural weathering, anthropogenic activities and sea water intrusion. Hence an attempt has been made in this study to delineate these processes and to identify the regions dominated by them. In this regard, 92 groundwater samples were collected and analysed for major cations and anions. Among the analysed parameters the ratios of the cations like Ca/Mg, (Ca + Mg)*/HCO3:(Na + K)*/HCO3 were used to identify the process of weathering. Moreover, the ternary plots of cations and selected anions were also used to identify the weathering and the anthropogenic processes. HCO3 − and SiO2 in groundwater were used to unravel the nature of weathering, supported by pH and pCO2 observations. HCO3 −-derived by the carbonate dissolution and silicate weathering were calculated from the total HCO3 − and it was found that HCO3 − derived from the carbonate rock dissolution is dominant in alluvium, tertiary and cretaceous formations due to the presence of kankar, calcareous sandstone and limestone. The (HCO3 + SiO2)/(Cl + NO3) ratios were used to demarcate the regions of weathering and anthropogenic activities and it was found that the central and north eastern part of the study area is dominated by the anthropogenic activities.